COLLABORATIVE LEARNING ON MATHEMATICAL CRITICAL THINKING SKILLS - Tri Wahyudi; Noerhasmalina Noerhasmalina; Dwi Desmayanasari; Fitria Lestari (Hipotenusa Journal of Research Mathematics Education (HJRME), 2022)
This research is quasi experiment with research design "Posttest Only Control Group Design" which aims to determine the application influence of collaborative learning models on the critical thinking ability students i.e. case study on grade VIII even semester SMP 1 Kelumbayan Barat Tanggamus. Sampling techniques using Cluster Random sampling. The research sample consists of two classes, namely one class experiment class i.e. grade VIII B as many as 39 students and one class control class VIII A as many as 40 students. Data collection techniques are obtained through mathematical critical thinking tests, observations, and interviews. Based on the results of the analysis obtained that tcount = 3.39. Distribution table, at the level of 5% obtained tdaf = 1,667 and at the level of 1% tdaf = 2,382. Proven tcount > ttable. It can be concluded that the collaborative learning model affects the ability of mathematical critical thinking students. The average mathematical critical thinking ability of students who use the collaborative learning model is higher than the average mathematical critical thinking ability of students who use the conventional learning model.